Multi-omics integration identifies NK cell-mediated cytotoxicity as a therapeutic target in systemic lupus erythematosus - Zhang, Jingjing; Ma, Ling; Deng, Hanyin; Yi, Wenqian; Tohtihan, Alim; Tang, Xiaojun; Wu, Xiudi; Feng, Xuebing (Frontiers in Immunology, 2025)
BackgroundSystemic lupus erythematosus (SLE) is an autoimmune condition that impacts various organs. Given the intricate clinical progression of SLE, it is imperative to explore novel avenues for precise diagnosis and treatment.MethodsPeripheral blood mononuclear cells (PBMC) were isolated from 6 SLE patients before and after treatment, 7 healthy controls and 7 disease controls. Assay for Transposase Accessible Chromatin with high throughput Sequencing (ATAC-seq) was used to analyze the chromatin accessibility signatures and RNA-seq was used to identify the differentially expressed genes, mRNA, lncRNA, circRNA, miRNA. Then ATAC-seq and RNA-seq were integrated to further analyze hub genes and pathways. Finally, we validated gene expression levels and examined changes in key genes after treatment through in vitro experiments.ResultsOur analysis reveals dynamic changes in chromatin accessibility during the course of disease progression in SLE. Significantly higher numbers of differentially accessible regions, transcripts, genes, mRNA, lncRNA, circRNA, and miRNA were observed in SLE patients compared to other cohorts, with these variances markedly reduced post-treatment. Two gene clusters associated with SLE disease improvement were identified, with a total of 140 genes intersecting with ATAC results. Pathway analysis revealed that NK cell mediated cytotoxicity was the most differentiated and therapeutically altered pathway in SLE patients. Independent sample validation confirmed that the gene expression of this pathway was reduced in SLE patients and associated with disease activity, whereas hydroxychloroquine (HCQ) effectively elevated their expression in vitro.ConclusionOur findings suggest that these NK cell signature genes may be associated with the complex pathogenesis of SLE. The restoration of NK cell-mediated cytotoxicity may serve as a useful marker of improvement following SLE treatment.